2020
DOI: 10.1192/bjb.2020.35
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness and cost-effectiveness of integrating mental health services in primary care in low- and middle-income countries: systematic review

Abstract: Aims and method This systematic review examines the effectiveness and cost-effectiveness of behavioural health integration into primary healthcare in the management of depression and unhealthy alcohol use in low- and middle-income countries. Following PRISMA guidelines, this review included research that studied patients aged ≥18 years with unhealthy alcohol use and/or depression of any clinical severity. An exploration of the models of integration was used to characterise a typology of behavioural health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 66 publications
(135 reference statements)
0
32
0
8
Order By: Relevance
“…Although not a primary focus, this review also highlighted the dearth of cost effectiveness evidence for psychosocial treatments delivered by NSHW [ 12 ]. Cubillos et al (2020) [ 64 ] noted that investments in programs for integrating behavioural health services into primary care using task-sharing and collaborative/stepped care approaches yielded cost-effective estimates in LMIC settings. The latter review also noted that cost savings were reported when a societal perspective was used in economic evaluations, pointing to the importance of inclusion of broader costs in these economic evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…Although not a primary focus, this review also highlighted the dearth of cost effectiveness evidence for psychosocial treatments delivered by NSHW [ 12 ]. Cubillos et al (2020) [ 64 ] noted that investments in programs for integrating behavioural health services into primary care using task-sharing and collaborative/stepped care approaches yielded cost-effective estimates in LMIC settings. The latter review also noted that cost savings were reported when a societal perspective was used in economic evaluations, pointing to the importance of inclusion of broader costs in these economic evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…Integration of mental health services into mainstream services has been recommended globally [47], and this has been found to be both effective for intended treatment outcomes, as well as economically cost-effective [21,48]. While treatment effectiveness benefits the patients, cost-effectiveness has a direct benefit on the health system and an indirect benefit to the patients as the quality of treatment can be improved as more resources are available.…”
Section: Integrating Mental Health Into Mainstream Primary Health Car...mentioning
confidence: 99%
“…Cubillos presented a preliminary review of 58 articles representing studies evaluating integrated mental health care in primary care settings in LMICs, with evidence to suggest that integration of mental health services improves outcomes for depression and alcohol use and is cost effective. Based on the review, Cubillos outlined a new typology of models of behavioral health integration that have been used in LMICs, including mental health care delivery by skilled and nonskilled mental health and primary care staff [ 61 ].…”
Section: Integrating Technology Into Practicementioning
confidence: 99%